SYNTHESIS AND IN VITRO LEISHMANICIDAL AND CYTOTOXIC ACTIVITIES OF 2-STYRYLQUINOLINES ANALOGS - MESA, Ana M.; MOLANO M., Paula A.; SEON, Blandine; FIGADERE, Bruno; ROBLEDO, Sara M.; MUÑOZ, Diana L.; SÁEZ V., Jairo A. (Vitae, 2009)
The search of new treatments for leishmaniasis is an active task nowadays, since there is a lack of nontoxic, cheap and non-resistant medication. In the literature several quinolines have shown in vitro activity against agents of cutaneous leishmaniasis, visceral leishmaniasis, African trypanosomiasis and Chagas diseases. Six 2-styrylquinolines derived from galipeine were synthesized by Perkin condensation of quinaldine with aromatic aldehydes. Leishmanicidal activity was estimated for Leishmania panamensis at the amastigote form and cytotoxic activity against U-937 cells. All compounds showed activity against both L. panamensis and U-937 cells. (E)-2-(2,5-dimethoxyphenyl)ethenyl)quinoline (1), (E)-2-(2,3- dimethoxyphenyl)ethenyl)quinoline (2) and (E)-N-[4-(2-quinolin-2-yl-ethenyl)phenyl]acetamide (3) were more active against axenic (EC50= 3.7, 4.5 and 19.1μg/mL) and intracellular amastigotes (EC50= 1.4, 1.8 and 1.7μg/ml, respectively), in comparison with hydrogenated derivatives 2-[2-(2,5-dimethoxy phenyl)ethyl]quinoline (1a), 2-[2-(2,3-dimethoxyphenyl)ethyl]quinoline (2a) and N-[4-(2-quinolin- 2-ylethyl)phenyl]acetamide (3a) (CE50= 31.1, 23.6 and 59.3μg/mL, respectively). All compounds were also active against the U-937 cells. Styrylquinolines 1, 2 and 3 showed a LC50 of 3.7, 6.2 and 4.5μg/mL, respectively and the hydrogenated derivatives 1a, 2a and 3a showed a LC50 of 16.0. 12.9 and 20.2μg/mL, respectively. Although hydrogenation reduced the leishmanicidal and cytotoxic activities, the activity showed against Leishmania parasites suggests this compound series has potential as drug candidates for the treatment of leishmaniasis.